Balances of Power, Threat, and Interests: The Logic behind China-Russia Strategic Alignment in the Post-Cold War Period - A. N. Korolev (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
Since the collapse of the Soviet Union, China-Russia relations have demonstrated a significant and consistent progress on a number of issues advancing to the strategic alliance. However, the existing explanations of such progress have rarely gone beyond simple recognition of the continuous deterioration of relations between these countries and the West, particularly the United States. However, such explanations seem insufficient since they do not reveal the key determinants of the Russian-Chinese alignment and cannot help assess the sustainability of this trend. In order to provide a comprehensive and methodologically consistent assessment of the main drivers of the China-Russia relations within the framework of the post-Cold War international system evolution, this paper draws on the latest findings in the theory of international alliances. To this end, the author harnesses the epistemological potential of the three main approaches to the root causes of interstate strategic alliances, namely the ‘balance of power’, the ‘balance of threat’ and the ‘balance of interests’. The paper examines the Russian-Chinese cooperation both within the framework of each of these three balances separately and in their interrelatedness and interdependence. The author shows that trend towards a closer strategic cooperation between China and Russia in the post-Cold War period stemmed from the inner dynamics of all of these balances. This strategic alignment is based on a complex of shared views on the United States as the main source of threats for national security and the commitment of both states to the idea of a multipolar world. The author concludes that not only will the trend towards strengthening Russian-Chinese cooperation continue, at least in the medium term, but it can receive a new impetus to evolve into a full-fledged alliance.